A publication dedicated to the cause of justice as it is to the nourishment of critical thinking - Headley, Bernard (Social justice, 1999)
Part of a special issue celebrating 25 years of this journal. The writer discusses the dedication of this journal to the cause of justice and to the nourishment of critical thinking. He maintains that this journal provided the critical sociological imagination that he sought. He observes that Social Justice has followed a policy of pushing, supporting, and wanting to improve virtually every writer who submitted work to the publication.